Rhythmic Architecture of Munalu in Gayo Becanang: Ostinato, Interlocking Patterns, and Ensemble Structure in a Traditional Music Practice - Berlian Denada; Erlinda Sofyan; Firas Trabelsi (Universitas Negeri Surabaya, 2026)
Becanang is a traditional Gayo musical practice with both musical and social functions in communal life. Although Becanang has been addressed in previous studies, musicological documentation of the rhythmic structure of the “Munalu” repertoire remains limited, particularly in relation to notation transcription and inter-instrumental analysis. This article examines the rhythmic structure of Munalu as performed by Sanggar Gayo Nusantara Etnik, Bener Meriah. The study employs a qualitative-descriptive approach with musicological and ethnomusicological perspectives. Data were obtained through field observation, video documentation conducted on 22 August 2025 in Bener Meriah, field notes, and observation of ensemble performance. The analysis involved repeated listening, measure segmentation, instrumental pattern identification, and transcription into staff notation. The findings show that Munalu is constructed through layered rhythmic patterns involving three Suling Gayo, three Canang, one Momong, one Gong, and two Gegedem. Its structure is organized through ostinato repetition, rhythmic-timbral markers, and interlocking patterns. This article contributes to the documentation of Gayo traditional music through rhythmic transcription and analysis.